Efficiency and timing performance of the MuPix7 high-voltage monolithic active pixel sensor - Augustin, Heiko; Berger, Niklaus; Dittmeier, Sebastian; Grzesik, Carsten; Hammerich, Jan; Hartenstein, Ulrich Benedikt; Huang, Qinhua; Huth, Lennart; Immig, David; Kiehn, Moritz; Kozlinskiy, Alexandr; Meier Aeschbacher, Frank; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2018)
The MuPix7 is a prototype high voltage monolithic active pixel sensor with 103×80μm2 pixels thinned to 64 μm and incorporating the complete read-out circuitry including a 1.25 Gbit/s differential data link. Using data taken at the DESY electron test beam, we demonstrate an efficiency of 99.3 % and a time resolution of 14 ns. The efficiency and time resolution are studied with sub-pixel resolution and reproduced in simulations.
Gesehen am 10.06.2020